Phase stabilization by electronic entropy in plutonium - N. Harrison (Nature Portfolio, 2019)
Plutonium has strong electronic correlations, which makes it difficult to establish microscopic understanding of the complicated structural phase diagram. Here the authors identify an electronic contribution to the entropy that stabilises the δ-Pu phase.